Synthetic strategies of supported atomic clusters for heterogeneous catalysis - Hongpan Rong (Nature Portfolio, 2020)
Supported atomic clusters with precise nuclearity are intermediate states between single-atom catalysts and nanoparticles in size. Here the authors summarize and discuss synthetic strategies of supported atomic clusters with unique catalytic properties for heterogeneous reactions.